Austerity and old-age mortality in England: a longitudinal cross-local area analysis, 2007–2013. (March 2016) - Loopstra, Rachel; McKee, Martin; Katikireddi, Srinivasa Vittal; Taylor-Robinson, David; Barr, Ben; Stuckler, David
Objective: There has been significant concern that austerity measures have negatively impacted health in the UK. We examined whether budgetary reductions in Pension Credit and social care have been associated with recent rises in mortality rates among pensioners aged 85 years and over. Design: Cross-local authority longitudinal study. Setting: Three hundred and twenty-four lower tier local authorities in England. Main outcome measure: Annual percentage changes in mortality rates among pensioners aged 85 years or over. Results: Between 2007 and 2013, each 1% decline in Pension Credit spending (support for low income pensioners) per beneficiary was associated with an increase in 0.68% in old-age mortality (95% CI: 0.41 to 0.95). Each reduction in the number of beneficiaries per 1000 pensioners was associated with an increase in 0.20% (95% CI: 0.15 to 0.24). Each 1% decline in social care spending was associated with a significant rise in old-age mortality (0.08%, 95% CI: 0.0006–0.12) but not after adjusting for Pension Credit spending. Similar patterns were seen in both men and women. Weaker associations observed for those aged 75 to 84 years, and none among those 65 to 74 years. Categories of service expenditure not expected to affect old-age mortality, such as transportation, showed no association. Conclusions: Rising mortality rates among pensioners aged 85 years and over were linked to reductions in spending on income support for poor pensioners and social care. Findings suggest austerity measures in England have affected vulnerable old-age adults.